Quantitative CT measures of pulmonary vascular volume distribution in pulmonary hypertension associated with COPD: Association with clinical characteristics and outcomes - Hector R. Cajigas; Ben Lavon; William Harmsen; Patrick Muchmore; Joana Costa; Charles Mussche; Sydney Pulsipher; Jan De Backer (Pulmonary Circulation, 2023)
Abstract To determine whether quantitative computed tomography (qCT)‐derived metrics of pulmonary vascular volume distribution could distinguish chronic obstructive pulmonary disease (COPD) subjects with associated pulmonary hypertension (PH) from those without and to characterize associations of these measurements with clinical and physiological characteristics and outcomes. We collected retrospective CT, pulmonary hemodynamic, clinical, and outcomes data from subjects with COPD and right‐heart catheterization‐confirmed PH (PH‐COPD) and control subjects with COPD but without PH. We measured the volumes of pulmonary vessels < 5 and >10 mm2 in cross‐sectional area as a percentage of total pulmonary vascular volume (qCT‐derived volume of pulmonary vessels < 5 mm2 in cross‐sectional area as a volume fraction of total pulmonary blood volume [BV5%] and qCT‐derived volume of pulmonary vessels > 10 mm2 in cross‐sectional area [BV10] as a volume fraction of total pulmonary blood volume [BV10%], respectively) using Functional Respiratory Imaging (FRI), an automated qCT platform, and compared them between PH and control arms and between subjects with mild‐moderate PH and those with severe disease. Correlations of hemodynamics with pulmonary function and associations with survival were tested. Forty‐five PH‐COPD and 42 control subjects were studied. BV5% was lower in PH subjects (32.2% vs. 37.7%, p = 0.003), and BV10% was higher (50.2% vs. 43.5, p = 0.001). Subjects with severe PH did not differ from those with mild‐moderate PH in qCT. Pulmonary vascular volumes were not associated with pulmonary function. BV10 was associated with mean pulmonary artery pressure (r = 0.3, p = 0.05). Associations with survival were observed for BV5% (hazard ratio 0.63, p = 0.02) and BV10% (hazard ratio 1.43, p = 0.03) in the PH‐COPD arm, but not for controls. qCT‐derived measures of pulmonary vascular volume may have diagnostic and prognostic significance in PH‐COPD and should be investigated further as screening and risk stratification tools